To humanize or not to humanize? That is the question: Socio-legal implications of social robots for patient care - Coaquira-Flores, Angel Jeancarlo (2025)
The influence of Artificial Intelligence (AI) and robotics in absolutely every area of ​​human activity, coupled with the COVID pandemic and the widening demographic gap between the elderly population and the availability of human talent in the healthcare sector, have necessitated the use of social robots within the healthcare sector. While it is true that social robots' physical appearance and ability to interact have made them seemingly ideal for use with patients such as adults with intellectual or psychosocial disabilities, it is imperative to analyze the legal and social issues arising from the deployment of this type of robot in the healthcare field. Thus, the main social problems encountered were: the resizing of the relationships generated in healthcare centers, patient distrust of autonomous systems, and the dangers arising from the humanization of robotics. Finally, at the legal level, issues such as the potential leakage of sensitive data throughout the life cycle of robots and the confusing relationship between accidents caused by machines and civil liability became evident.